Labor and economic reforms in Latin America and the Caribbean. - World Bank. (Washington, D.C. : World Bank, 1995)
"Discusses impact of economic policy and performance on well-being o f region's workers. Focuses on impact of policy reforms on labor market s in 1980s-90s. Concludes that countries with well-established reforms will experience significant gains for their workers"--Handbook of Latin American Studies, v. 57.
"This report was prepared in conjunction with World development repo rt 1995: workers in an integrating world"--P. iv.
Includes bibliographical references (p. 27-28).
Keywords: Labor policy -- Latin America; Labor policy -- Caribbean Area; Latin America -- Economic policy; Caribbean Area -- Economic policy